The police competence to ensure the rights and freedoms of citizens in modern society - Кубаєнко, Андрій Володимирович; Кубаєнко, А. В.; Кубаенко, Андрей Владимирович; Kubaienko, Andrii V.; Охріменко, Іван Миколайович; Охріменко, І. М.; Охрименко, Иван Николаевич; Okhrimenko, Ivan M.; Крижановська, Олена Володимирівна; Крижановська, О. В.; Крыжановская, Елена Владимировна; Kryzhanovska, Olena V.; et al. (Universidad del Zulia, 2021)
The aim of the study is to form a systematic approach to understanding and resolving a set of tasks of police activities that guarantee the rights and freedoms of citizens in modern society. It was concluded that the most typical negligence in this area includes violations of the rights and freedoms of citizens such as the installation of administrative actions against them without any sign of the crime, incorrect characterization of administrative infractions, the violation of the procedural order of administrative detention, cases of unjustified detention without preparation of reports, as well as exceeding the legal deadlines for administrative detention. Particular attention was paid to the set of means of appeal in proceedings concerning administrative offences, which may be referred to as the institution of the protection of citizens’ rights and freedoms. Common European approaches to the legal regulation of policing and the influence of European Union law and decisions of the European Court of Human Rights on the guarantee of human rights and freedoms in policing were analyzed.

Метою дослідження є формування системного підходу до розуміння та вирішення комплексу завдань діяльності поліції, що гарантують права і свободи громадян у сучасному суспільстві. Зроблено висновок, що найбільш типовою недбалістю у цій сфері є порушення прав і свобод громадян, такі як притягнення до них адміністративних дій без ознак злочину, неправильна кваліфікація адміністративних правопорушень, порушення процесуального порядку адміністративного затримання, випадки безпідставного затримання без складання протоколів, а також перевищення встановлених законом строків адміністративного затримання. Особливу увагу було приділено комплексу засобів оскарження у провадженні про адміністративні правопорушення, які можна назвати інститутом захисту прав і свобод громадян. Проаналізовано загальноєвропейські підходи до правового регулювання діяльності поліції та вплив права Європейського Союзу та рішень Європейського суду з прав людини на гарантування прав і свобод людини у поліцейській діяльності.
Kubaienko A. The police competence to ensure the rights and freedoms of citizens in modern society / A. Kubaienko, I. Okhrimenko, O. Kryzhanovska, I. Kislitsyna, M. Hryshchenko // Cuestiones Políticas. - Vol. 39. - Issue 69. - Universidad del Zulia, 2021. - P. 164-181.
Keywords: administrative law; human rights; rule of law; police; protection of citizens’ rights; адміністративне право; права людини; верховенство права; поліція; захист прав громадян; Research Subject Categories::LAW/JURISPRUDENCE